2009
DOI: 10.1007/s00404-009-0966-7
|View full text |Cite
|
Sign up to set email alerts
|

Severity of pain and circadian changes in uterine artery blood flow in primary dysmenorrhea

Abstract: Uterine artery blood flow is reduced at night in dysmenorrhea cases. In correlation with this, the cases feel more pain at night. Our results may be important on the planning of working hours and their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
0
10
2
1
Order By: Relevance
“…A similar reflex response exists in humans, increasing uterine blood flow by reducing sympathetic activity on vasoconstrictor fibres that innervate the uterus[25, 54]. Uterine blood flow is often reduced in women with primary dysmenorrhea[55, 56] and increasing uterine blood flow appears to be related to some of the analgesic benefits of acupuncture in primary dysmenorrhea[50, 57]. The magnitude of the impact of needling SP6 and, to a lesser extent, REN4 and SP8, may be larger than stimulation-specific differences.…”
Section: Discussionmentioning
confidence: 99%
“…A similar reflex response exists in humans, increasing uterine blood flow by reducing sympathetic activity on vasoconstrictor fibres that innervate the uterus[25, 54]. Uterine blood flow is often reduced in women with primary dysmenorrhea[55, 56] and increasing uterine blood flow appears to be related to some of the analgesic benefits of acupuncture in primary dysmenorrhea[50, 57]. The magnitude of the impact of needling SP6 and, to a lesser extent, REN4 and SP8, may be larger than stimulation-specific differences.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Reversing the vasoconstriction caused by prostaglandins in women with dysmenorrhea decreases menstrual pain. 24,25 Reversing the vasoconstriction caused by prostaglandins in women with dysmenorrhea decreases menstrual pain.…”
Section: Discussionmentioning
confidence: 99%
“…Menstrual pain is strongly correlated with reductions in uterine blood flow. 13 Stener-Victorin et al 12 found a dose-response relationship between the number of EA treatments and increases in uterine blood flow, which may also be relevant for menstrual pain. There is also evidence of a dose-response relationship when acupuncture and related techniques are used for non-gynaecological pain conditions 14 or subfertility.…”
Section: Introductionmentioning
confidence: 99%